Immersive Learning - Stylianos Mystakidis; Vangelis Lympouridis (Encyclopedia, 2023)
Immersive learning conceptualizes education as a set of active phenomenological experiences that are based on presence. Immersive learning can be implemented using both physical and digital means, such as virtual reality and augmented reality.